The development of competition law in Kosovo - Novitet Xh. Nezaj (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
Competition law is a pillar of a market economy and determines the quality of economic life. This paper explores the origin and development of competition law in Kosovo. It deals with constitutional developments. It attempts to explore how Kosovo's Constitution expresses crucial provisions regarding competition law. Additionally, it takes a broad approach to the relevance of EU competition law for Kosovo. It discusses specific aspects of EU competition law, and the implications of the changes required by the Stabilization and Association Agreement (SAA). This paper seeks to address these aspects by developing theoretical approaches and conceptual tools that can enable the implementation of the SAA's provisions.
Keywords: 320; competition; SAA; approximation; enforcement; competition authority